2020
DOI: 10.1002/er.5774
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of seafood industrial wastewater coupled with electricity production using air cathode microbial fuel cell under saline condition

Abstract: The present study investigated seafood industrial wastewater treatment with corresponding power generation in air cathode microbial fuel cell under saline condition (40 g/L). The results recorded total chemical oxygen demand) removal of 52 ± 1.8%, 64 ± 1.1%, 85 ± 1.2%, 89 ± 1.4%, and 76 ± 1.2% to the corresponding organic load (OL) of 0.5, 0.75, 1, 1.25, and 1.5 gCOD/L under saline condition. Soluble chemical oxygen demand reduction was in the range of 46% to 78% at OL of 0.5 to 1.5 gCOD/L. The maximum power d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Halophilic sediments such as CJ have shown in previous works their efficiency in designing halotolerant bioanode able to degrade azo dyes in textile wastewater with more than 90% of COD removal rate (Askri et al, 2020). Moreover Pugazhendi et al (2020) reached a COD removal efficiency of up to 89% when used halophilic microorganisms to treat seafood industrial wastewater. Similarly, Feng et al (2015) reported enhanced removal of recalcitrant p-Fluoronitrobenzene when a MEC was operated at highly saline conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Halophilic sediments such as CJ have shown in previous works their efficiency in designing halotolerant bioanode able to degrade azo dyes in textile wastewater with more than 90% of COD removal rate (Askri et al, 2020). Moreover Pugazhendi et al (2020) reached a COD removal efficiency of up to 89% when used halophilic microorganisms to treat seafood industrial wastewater. Similarly, Feng et al (2015) reported enhanced removal of recalcitrant p-Fluoronitrobenzene when a MEC was operated at highly saline conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Reference [17] show the use of two-chamber MFC to generate 107% electrical energy compared to the operational energy needed with overall Chemical Oxygen Demand (COD) removal of 91.88% in a brewery wastewater plant. References [18] show that air cathode MFC made up of carbon brush anode with twisted titanium wire and platinum-coated carbon cloth cathode managed to remove 89+1.4% of total COD and 78+1.5% of soluble COD at 1.25 organic load of seafood processing industry in Saudi Arabia with the highest power density of 530 + 2.4 mW/m 2 .…”
Section: B Advantages and Disadvantages Of The Mfcmentioning
confidence: 99%
“…In another study, seafood industry wastewater was treated using a microbial fuel cell under saline conditions. The results showed COD removal of 85% to the organic load of 1.25 g COD/L under saline conditions [16].…”
Section: Introductionmentioning
confidence: 95%